Highly Pathogenic Avian Influenza A(H5N1) Clade 2.3.4.4b Virus in Domestic Cat, France, 2022 - Briand, François-Xavier; Souchaud, Florent; Pierre, Isabelle; Beven, Véronique; Hirchaud, Edouard; Hérault, Fabrice; Planel, René; Rigaudeau, Angélina; Bernard-Stoecklin, Sibylle; Van der Werf, Sylvie; Lina, Bruno; Gerbier, Guillaume; et al. (Emerging infectious diseases, 2023)
We detected highly pathogenic avian influenza A(H5N1) clade 2.3.4.4b virus in a domestic cat that lived near a duck farm infected by a closely related virus in France during December 2022. Enhanced surveillance of symptomatic domestic carnivores in contact with infected birds is recommended to prevent further spread to mammals and humans.